Efficiency test of a General Electric Co. variable speed Form M induction motor - Cowles, Alson J.; Claudius, Stewart (My University, 1907)
Introduction: At the present day the high cost of copper makes it imperative that the line construction for the transmission of power should be such as to require a minimum amount of copper. This condition is obtained by raising the voltage at which the power is transmitted. Since alternating current is the most adaptable for this work, it is being used more and more. For this reason alternating current motors have become one of the largest problems in the electrical industry. There are at the present time two general classes of alternating current motors, the synchronous motor and the induction motor. The synchronous motor does very well in sub-stations and power houses where it may be readily started. It gives a constant speed and by its use the power factor of a line may be improved, but the disadvantages due to requirements of an exciter and a means of starting, prohibit its installation in small units or in isolated places.
Citation: Cowles, Alson J. and Claudius, Stewart. Efficiency test of a General Electric Co. variable speed Form M induction motor. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Induction Motor; Efficient Test; Motor Testing; General Electric Company; Theses